Unmasking delayed recovery in severe diabetic ketoacidosis: clinical and biochemical clues from early resuscitation - Jaeeun Chung; Bina Kim; Chong Kun Cheon; Jeong-Eun Kang; Younga Kim; Sukdong Yoo (Annals of Pediatric Endocrinology & Metabolism, 2026)
Purpose: This study aimed to explore how the rate of acidosis correction relates to initial clinical status, treatment needs, and short-term outcomes in severe diabetic ketoacidosis (DKA).Methods: This retrospective study reviewed records of patients aged 1–18 with severe DKA admitted to a single tertiary center (January 2009–March 2023). Patients whose pH rose ≥0.05 within 6 hours were assigned to the early recovery group (ERG); the remainder were assigned to the delayed recovery group (DRG). Statistical analyses included group comparisons and regression models to assess clinical and biochemical factors.Results: Fifty admissions met inclusion criteria (ERG n=39; DRG n=11). Compared with the ERG, DRG patients were older (median: 14.1 years vs. 11.8 years) and showed greater weight loss, more altered mentation, and more hyperosmolar presentations, though differences were not significant. Initial laboratory results in the DRG revealed lower pH and bicarbonate with higher blood urea nitrogen (BUN), creatinine, and C-reactive protein, indicating deeper hypovolemia and inflammation. Despite similar guideline-based fluids and insulin, the DRG gained less weight in 24 hours, suggesting underestimation of fluid deficit. Although the rate of pH improvement differed during the first 6 hours, pH values converged by 24 hours, and time to reach pH 7.30 did not differ significantly.Conclusion: This study clarifies the natural course of acute severe DKA and highlights the importance of precise evaluation of fluid deficits. In patients with elevated BUN, creatinine, and CRP levels, timely and appropriate fluid management strategies are essential to improve outcomes.